Tyrolis Latina Geschichte der lateinischen Literatur in TirolBand I: Von den Anfängen bis zur Gründung der Universität InnsbruckBand II: Von der Gründung der Universität Innsbruck bis heute - Korenjak, Martin (2012)
In the territory of historical Tyrol (i.e., the present Austrian province of Tyrol, South Tyrol, and Trentino), a huge number of Latin texts has been written from the Early Middle Ages to the 21th century. A good part of this literature has been preserved as manuscripts or printed books in the libraries and archives of monasteries, schools, universities, cities and other institutions. The present history of literature for the first time gives a systematic overview of these writings and describes them according to historical eras and literary genres. The single eras are separated from each other by events that had a massive impact on the conditions of production and reception of Latin literature in Tyrol. Each era is first generally characterised in historical and cultural terms; after that, its Latin poetry, rhetoric and eloquence, historiography, biography, epistolography, theology and other ecclesiastic writings, philosophy, medicine, natural sciences, law and jurisprudence are treated in single chapters. The literary history consists of two volumes. The first one includes the eras "From the beginnings to the unification of Tyrol under Count Meinhard II. (1285)", "From the unification of Tyrol to the death of Emperor Maximilian I. (1519)", "The 16th century until the death of Ferdinand II., Archduke of Further Austria (1595)", and "The 17th century until the extinction of the Tyrolian line of the Habsburgs (1665) and the foundation of the University of Innsbruck (1669)". The second volume comprises the eras "From the foundation of the University of Innsbruck to the abolition of the Jesuit order (1773)", "From the expulsion of the Jesuits to the revolution of the year 1848", and "From the revolution of 1848 until the present day" as well as the bibliography and the indexes.